Breathing and Dying in 2020 - Anita Chary (University of Edinburgh Library, 2021)
Every ethnographer balances participation and observation during fieldwork in their own unique way. For those whose primary role is participation, field notes represent an avenue for reflecting on trends that may not be immediately obvious when one is mired in the ethnographic setting. The author, an emergency physician and anthropologist, reflects on racial injustices and transformations in biomedical rituals to do with death and dying, from the front lines of the COVID-19 pandemic.